Os efeitos da gestão dos recursos, da orientação empreendedora e das capacidades do desempenho organizacional: um estudo no setor metalmecânico da Serra Gaúcha - Dias, Deise Taiana de Ávila (My University, 2019)
The main aim of this thesis was to propose and check a conceptual model for organizational performance of small and medium sized firms, outlining key factors that contribute to the performance of these enterprises in the Metal-mechanical sector at Serra Gaúcha, in the South region of Brazil. The theoretical basis of this research was composed by Resource-based theory and Dynamic Capability Theory. The constructs investigated were: organizational performance, management of resources, entrepreneurial orientation, managerial capacity, market orientation capacity and pricing capability. The research ambience attained small and medium Metalmechanical firms, in which this investigation was applied to its managers. A descriptive quantitative research was conducted using a structured questionnaire, based on an applied survey with cross section and the data the data were analyzed from the Modeling of Structural Equations. Results showed that the organizational performance was explained by 71.2% of the investigated constructs from this research, which the literature considers a strong explanation power. The constructs that greatest positive and significant impact on organizational performance were: (i) the market orientation capacity; (ii) the entrepreneurial orientation; and (iii) the pricing capability. It was observed that there is a relation between the following constructs: (i) managerial capacity and resource management; (ii) entrepreneurial orientation and managerial capacity; (iii) managerial capacity and market orientation capacity; and (iv) managerial capacity and pricing capability. Among the research findings, we highlight, firstly, the evolution of the understanding of which constructs influence the organizational performance; and secondly, the contribution of this thesis in a scientific way in this area of knowledge, adding new studies to the topic of organizational performance, with the purpose of encouraging the administration of resources and capabilities in the Metal-mechanical firms of the Serra Gaúcha.
O objetivo desta tese foi propor e testar um modelo conceitual do desempenho organizacional delineando os fatores-chave que contribuem para a performance de pequenas e médias empresas do setor metalmecânico da Serra Gaúcha, na região sul do Brasil. A base teórica desta pesquisa foi composta pela Teoria Baseada em Recursos e pela Teoria das Capacidades Dinâmicas. Os construtos investigados foram: desempenho organizacional; gestão dos recursos; orientação empreendedora; capacidade gerencial; capacidade de orientação para o mercado; e capacidade de precificação. A ambiência da pesquisa abrange pequenas e médias indústrias metalmecânicas, nas quais o estudo foi aplicado aos seus gestores. A pesquisa quantitativa descritiva foi conduzida por meio de um questionário estruturado, utilizando-se o levantamento de dados com o uso de uma survey de corte transversal, e os dados foram analisados a partir da Modelagem de Equações Estruturais. Os resultados indicaram que o desempenho organizacional foi explicado em 71,2% pelos construtos investigados, o que a literatura considera um forte poder explicativo. Os construtos que apresentaram maior impacto positivo e significativo no desempenho organizacional foram: (i) a capacidade de orientação para o mercado; (ii) a orientação empreendedora; e (iii) a capacidade de precificação. Observouse que há uma relação entre os seguintes construtos: (i) a capacidade gerencial e a gestão dos recursos; (ii) a orientação empreendedora e a capacidade gerencial; (iii) a capacidade gerencial e a capacidade de orientação para o mercado; e (iv) a capacidade gerencial e a capacidade de precificação. Dentre as contribuições deste estudo, destaca-se, primeiramente, a evolução da compreensão de quanto os construtos influenciam no desempenho organizacional; e, por segundo, a contribuição desta tese de maneira científica nessa área do conhecimento, agregando novos estudos ao tema do desempenho organizacional, com o intuito de incentivar as práticas de administração dos recursos e capacidades nas indústrias metalmecânicas da Serra Gaúcha.
Keywords: Desenvolvimento organizacional; Empreendedorismo; Pequenas e médias empresas - Serra, Região (RS); Organizational change; Entrepreneurship; Small business - Serra, Region (RS)